Updated Checklist and new records of the lady beetles (Coleoptera: Coccinellidae) from the Morelos state, Mexico - Trejo-Loyo, Adriana Gabriela; Nestor, Jorge; Marín-Jarillo, Antonio (Instituto de Ecología, A.C., 2024)
The state of Morelos in Mexico has been an important site for the collection and study of several groups of insects, including coccinellids; however, this group had not received enough attention, and for this reason there is not an updated list of species that includes the species recorded and those that are sheltered in national and state entomological collections.  The objective of this research was to contribute to the taxonomic knowledge of the ladybugs from the state of Morelos for which the specimens of Coccinellidae Latreille, 1807 deposited in three insect collections in the state of Morelos and three national ones, were reviewed. The entomological material was identified using dichotomic keys and information from scientific articles, which is why in some species it was necessary to extract the genitalia of the males. A bibliographic review was carried out to include the species recorded in isolated form. The list includes a total of 100 species, of which 19 are new records for the state. The validity of the record of the species Azya luteipes Mulsant, 1850, Paraneda pallidula guticollis Mulsant, 1850, Hyperaspis bicruciata Mulsant, 1850, H. sexverrucata (Fabricius, 1801), Scymnus (Pullus) apicalis Mulsant, 1850 and S. (Pullus) auritulus Mulsant, 1850 is questioned due to their current distribution.